Essential foundations of economics - Bade, Robin; Parkin, Michael , 1939- (Pearson series in economics, 2011)
This textbook provides an overview of microeconomic and macroeconomic theory. It presents a survey of the key lessons of economics -- demand, supply, pricing in markets, structure of markets, monetary policy, fiscal policy, international trade, and other key issues that arise in general discussion. It reviews the primary tools of economic thinking and covers the major themes that appear in the popular media